Visualization and Quantification of the Oral Hygiene Effects of Brushing, Dentifrice Use, and Brush Wear Using a Tooth Brushing Simulator - Ledder, Ruth G.; Latimer, Joe; Forbes, Sarah; Penney, Jodie L.; Sreenivasan, Prem K.; McBain, Andrew J. (Frontiers in Public Health, 2019)
Standardized, reproducible brushing regimes were applied to typodonts coated in simulated or biological plaques to assess the effects on tooth cleaning of toothbrush/dentifrice regimens. Replicated typodonts were coated with OccludeTM or GlogermTM indicators to simulate plaque, and brushed reproducibly using a mechanical brushing simulator to compare the cleaning of occlusal surfaces before and after brushing with water or a dentifrice. An in vitro model using salivary inocula to cultivate oral biofilms on typodont surfaces was then developed to evaluate removal of disclosed plaque by new toothbrushes in comparison to toothbrushes with wear equivalent to three months of use. Analyses of typodonts brushed under controlled conditions significantly (p<0.01) distinguished between brushed and unbrushed surfaces and between the use of water versus dentifrice for the removal of simulated interproximal plaque (p<0.05). New toothbrushes removed significantly (p<0.05) more biological plaque from typodont surfaces than brushes that had been worn by repeated brushing. Through controlled and defined brushing of typodonts with simulated and biological plaques, the effectiveness of dental hygiene regimens was compared under reproducible conditions. Data indicate that the cleaning effectiveness of brushing was augmented by the addition of dentifrice and that new brushes were significantly more effective than brushes with substantial wear from previous use.